EFFECT OF BIO-MOLECULES AND MULCHING PRACTICES ON FRUIT QUALITY PARAMETERS OF TOMATO HYB - SHIVANAND JAMMIHAL*, M. S. SHARADA and B.C. NARASIMHA PRASAD (The Journal of Research ANGRAU, 2022)
Quality of tomato fruits is extremely important from the consumer point of view. The pigmentsresponsible for tomato fruit colour offer several health benefits, the firmness of the fruit ensureslong distance transportation and reduce food wastage. Though there are several possibilities ofenhancing these quality traits in tomato fruits, few agronomic approaches seem to be cost effectiveand provides easy wins for growers and consumers. In this study, we have evaluated the influenceof mulching, humic acid, Lipo-chito-oligosaccharides and their interactive effects with differentgenetics in improving the fruit colour and firmness in tomato fruits. Better hue and Chroma valuesobserved in hybrid, Ashoka viz., 38.79% and 29.99%, respectively and highest transportability(10.2 days) was recorded in TO 1057. Effect of polythene mulch on transportability (10.5 days)showed significantly over crop mulch and no mulch treatments. Application of Ratchet @ 240 ml/acre showed better hue value (39.8%), Chroma value (28.42%) and transportability (9.22 days).It is concluded that genetics coupled with mulching and bio molecules provide significant benefitson improved quality of tomato fruits.